Comparison of Hearing Status of HIV‐Exposed and ‐Unexposed Newborns and Immunovirologic Correlates in HIV‐Exposed Newborns. (2nd September 2014) - Fasunla, Ayotunde J.; Nwaorgu, Onyekwere G.; Taiwo, Babafemi; Olaleye, David O.; Murphy, Robert L.; Adewole, Isaac F.; Akinyinka, Olusegun O.
Abstract : Objectives: (1) Compare hearing status of HIV‐exposed newborns with HIV‐unexposed newborns and (2) determine the association between their hearing threshold and maternal and newborn laboratory parameters. Methods: A cohort audiometric study of newborns in secondary and tertiary hospitals between October 2012 and September 2013. Subjects studied: Consecutive 126 HIV‐exposed and 121 HIV‐unexposed newborns. Interventions: Hearing screening and thresholds of the newborns were done with Auditory Brainstem Response and compared against maternal highly active antiretroviral therapy (HAART), CD4 cell counts, RNA viral loads, and newborn CD4 percentage. Outcome measurements: Hearing threshold levels of both groups were measured and analyzed using appropriate statistics. Results: A total of 9.5% of HIV‐exposed and 5% of unexposed newborns had hearing impairment ( P =. 1771; relative risk [RR] = 1.9206 [0.7445‐4.9549]). A total of 6.4% of HIV‐exposed and 2.5% HIV‐unexposed newborns had hearing threshold >20 dBHL ( P =. 1578). There was no significant association between the hearing threshold of HIV‐exposed newborn and maternal CD4 cell counts ( P =. 059) but there was a significant association with maternal viral load ( P =. 034). Study showed a significant difference in the hearing of the 119 HAART‐exposed newborns and 7 unexposed newborns ( P =. 002; RR = 0.13 [0.05‐0.32]). Conclusions: There was a trend toward more hearing loss in HIV‐exposed newborns and a significant difference between the hearing thresholds of HIV‐exposed newborns with CD4 % of ≤25 and >25. There is a significant association between newborn hearing threshold and mothers' viral load. This background information supports the need for further study on the role of in‐utero exposure to HIV and HAART in newborn hearing loss.